Modelling distribution and fate of coralligenous habitat in the Northern Adriatic Sea under a severe climate change scenario - Vitelletti, Maria Letizia; Manea, Elisabetta; Bongiorni, Lucia; Ricchi, Antonio; Sangelantoni, Lorenzo; Bonaldo, Davide (Frontiers in Marine Science, 2023)
Due to their well-acknowledged capability in predicting habitat distributions, Habitat Suitability Models (HSMs) are particularly useful for investigating ecological patterns variations under climate change scenarios. The shallow coastal regions of the Northern Adriatic Sea, a sub basin of the Mediterranean Sea, are studded with coralligenous outcrops recognized as important biodiversity hotspots exposed to the effects of climate change. In this research, we investigate the distributions of Northern Adriatic Sea coralligenous habitats characterized by diverse species assemblages differently influenced by the environmental factors, and provide a projection of how a severe climate change could impact them. Two models based on different machine learning HSM approaches (Random Forest and MaxEnt), populated with occurrence data gathered from previous publications, environmental parameters’ measurements from online databases (CMEMS, Bio-Oracle) and a set of dedicated ocean model simulations, are applied in recent past conditions and under a future severe (RCP8.5) climate change scenario. The model performance metrics confirm the ability of both approaches for predicting habitats distribution and their relationship with environmental conditions. The results show that salinity, temperature and nitrates concentration are generally the most important variables in influencing the coralligenous outcrops distribution. The environmental variations projected under climate change conditions are expected to facilitate the increase of opportunistic organisms, more tolerant to altered and stressful conditions, at the expense of more vulnerable species. This will result in a shift in this habitat distribution, with a consequent potential loss of biodiversity in the Northern Adriatic Sea.